The association between long-term longitudinal trends in guideline adherence and mortality in relation to age and sex - Frankenstein, Lutz; Remppis, Bjoern-Andrew; Flügel, Andrea; Dösch, Andreas; Katus, Hugo; Senges, Jochen; Zugck, Christian (European journal of heart failure, 2010)
Aims Using a large clinical multi-site prospective chronic heart failure registry, we sought to determine (i) implementation of guidelines over time and (ii) adjusted survival benefit there from. Methods and results Clinical characteristics, mortality, and medication according to guidelines [guideline adherence index (GAI) for ACE-inhibitors or angiotensin receptor blockers, beta-blockers, aldosterone antagonists] were compared for 1481 patients included from 1994 to 2000 and 1811 patients from 2001 to 2007. The co-morbidity corrected GAI significantly increased from 1994-2000 to 2001-07 (P < 0.001). Concomitantly, 1- and 3-year mortality decreased (14.1-4.8 and 29.5-10.9%, respectively, P < 0.001 each). No interaction with age or sex was noted (P = 0.06, P = 0.25, respectively), though age determined complete medication according to guidelines (P < 0.05). The GAI was a significant predictor of lower overall mortality (adjusted HR per 10% increase: 0.92; 95% CI: 0.88-0.97; P = 0.001), again independent from age or sex. Results were essentially unchanged after controlling for co-morbidities and other potential confounders. Conclusion This study shows that increased use of medication according to guidelines might occur without interventions targeting medication use. It seems to be associated with a substantial improvement in survival. Even though causality cannot be proven, the findings underscore the importance of meticulous implementation of guidelines irrespective of age, sex, or co-morbidities.